An analysis of purple truths: an alternative history of the school of journalism and media studies at Rhodes University. Exploring the possibilities of digital media for telling history through multiple voices - Geldenhuys, Jesamé (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
In theory, notions of public history and participatory journalism signal the ability of users to become active collaborators in the journalistic process with a degree of agency and authority over media content. Similarities in public history and participatory journalism are manifested in audience participation where the traditional and hegemonic boundaries between readers and journalists/historians are challenged. In this thesis, I present Purple Truths, a digital public history website about the School of Journalism and Media Studies at Rhodes University, that highlights multivocality and plurality. It allowed for democratisation of the historical narrative by inviting audience participation to historical inquiry on a digital platform. It was constructed as a case study for the thesis to investigate participatory processes. Using a five-dimensional model developed by Netzer et al. (2014) for the construction of participation on news websites, I identified five major participation features that revealed how and where participation was happening on the website. The features were mapped and tabulated according to Carpentier's (2011) maximalist/minimalist dimensions of participation (access, interaction and 'real') to determine the degrees of participation in this study towards the aim of using the Purple Truths website to democratise the historical narrative. My findings suggest that despite a diversity of strategies, the study did have to rely on existing norms and practices of editorial decision-making, even in the context of digital media, and significant stages of the news-production process (selection/filtering) remained in the hands of researcher/editor. Maximalist participation, demonstrated as equalised power relations in decision-making, has a utopian dimension and is difficult to translate into practice. However, participation research requires further investigation in the digital humanities in South Africa to explore notions of democratisation of the narrative in academic and social praxis as sites of interdisciplinary democratic renewal
Keywords: Citizen journalism -- South Africa -- Makhanda; Social media and history -- South Africa -- Makhanda; Public history -- South Africa -- Makhanda; Digital media -- South Africa -- Makhanda; Digital humanities; User-generated content -- South Africa -- Makhanda; Social media -- Authorship; Rhodes University. School of Journalism and Media Studies -- History; Purple Truths